Pengaruh Intangible Asset dan Tunneling Incentive terhadap Tax Avoidance dengan Profitabilitas sebagai Variabel Moderasi - Refi Fadilla, Meisya; Nuryati, Tutty; Rossa, Elia; Puspaningtyas Faeni, Dewi; Manrejo, Sumarno (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The purpose of this study was to determine the effect of intangible assets and tunneling incentive on tax avoidance and to determine whether profitability can moderate intangible assets and tunneling incentive on tax avoidance in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2022. The population in this study are food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2022. The research population is also included in the scale of multinational companies. Sampling in this study was conducted using a nonprobability sampling approach. The technique used to determine the sample in this study was purposive sampling. The type of data required in this study is secondary data in the form of financial statements. These results show different relationships between intangible assets and tunneling incentive on tax avoidance, as well as the relationship between profitability in moderating intangible assets and tunneling incentive on tax avoidance.